A Highly Efficient 18-40 GHz Linear Power Amplifier in 40-nm GaN for mm-Wave 5G - Mayeda, Jill C.; Lie, Donald Y. C.; Lopez, Jerry (IEEE microwave and wireless components letters, 2021)
A medium-power, highly-efficient broadband linear power amplifier (PA) is designed in a 40-nm GaN technology that covers the key 5G FR2 band of 24-40 GHz. Load-pull simulations suggest better device broadband performance and peak power-added-efficiency (PAE) around V_{\text {DD}} =4 -6 V. Measurement data corroborates the simulations and this PA achieves a small-signal 3-dB bandwidth (BW) of 18.0-40.3 GHz, with max. PAE/ P_{\text {SAT}} of 42.1%/18.6 dBm at 28 GHz, and 26.0%/17.2 dBm at 38 GHz at V_{\text {DD}} = 4 V. When tested with a 9 MHz × \,\, 100 MHz 256-quadratic-amplitude modulation (QAM) 5G new radio (NR) signal, it achieves an adjacent-channel-leakage-ratio (ACLR) of −27 dBc with P_{\text {OUT, AVG}} /PAE of 11.3 dBm/13.9% at 28 GHz. When compared with state-of-the-art broadband PAs, it achieves the best S_{21}~3 -dB BW with excellent peak PAE and linearity. This work also reports the best PAE for broadband medium-power millimeter-wave GaN PA at P_{\text {SAT}}~\sim 20 dBm.